2017
DOI: 10.4312/as.23.3.71-87
|View full text |Cite
|
Sign up to set email alerts
|

Education as habilitation: empirical examples from adjusted education in Sweden for students associated with high-functioning autism

Abstract: This article draws upon findings from an educational program in Information Technology for young adults associated with high-functioning autism. The aim of the program was to make the students employable. Data was collected through participant observation and research interviews. Of the twelve students who completed their education, five had made transitions to employment and three held internship places. Because of this training and the adaptations that were made within the educational program, the well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In previous research, the opportunity to be able to study alone at one's own designated study cubicle, to focus on one task at a time, and to enjoy the freedom to decide over one's time has been shown to be of great import to the success of the academic endeavours of young people with high-functioning autism [45,46]. In addition to formal learning experiences linked to subject content, informal learning experiences also take place.…”
Section: High-functioning Autismmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous research, the opportunity to be able to study alone at one's own designated study cubicle, to focus on one task at a time, and to enjoy the freedom to decide over one's time has been shown to be of great import to the success of the academic endeavours of young people with high-functioning autism [45,46]. In addition to formal learning experiences linked to subject content, informal learning experiences also take place.…”
Section: High-functioning Autismmentioning
confidence: 99%
“…Such experiences can include social skillssocial learning, which are of particular importance to people with high-functioning autism [21][22][23][24]. Previous research [45,46] has also shown the importance of social learning and the opportunities that it provides for people with high-functioning autism, since it allows them to develop the ability to create social relationships and networks, and gives them the courage to ask for help and to speak in front of groups of people. Social learning can also be linked to formal learning and thereby constitute a teaching subject which can be given complementary to more informal social learning experiences.…”
Section: High-functioning Autismmentioning
confidence: 99%
See 1 more Smart Citation